Composition and microbiological quality of raw milk refrigerated in community tanks (Research, Society and Development, 2021)
Milk is rich in nutrients, but several factors in the production system interfere with its quality. The objective of this study was to analyze the composition and microbiological quality of raw milk stored in community tanks from the municipality of Aricanduva – Minas Gerais. Samples were collected from eight community tanks at different properties. The milk composition and temperature were analyzed using the digital milk analyzer. The total count of aerobic mesophilic microorganisms was performed at the Laboratory of Science and Technology of Products of Animal Origin, Department of Animal Science, Federal University of Vales do Jequitinhonha and Mucuri, Diamantina – Minas Gerais. The data obtained were compared to the values established by Normative Instruction (IN) n° 76, by means of Student's t-test and Wilcoxon's non-parametric test at the level of 5% of significance. The average levels of fat (3.55 g/100g), protein (3.00 g/100g), lactose (4.45 g/100g) and total solids (11.76 g/100g) were within the standards minimum required. The content of defatted solids (8.21 g/100g) was the limiting factor to the compliance with IN76, with an average value lower than that established (8.40 g/100g). The temperature of the milk was higher than the standard required by the legislation and the count of mesophilic microorganisms did not differ from the legislation. It is concluded that the composition of raw milk stored in community tanks in the municipality of Aricanduva – Minas Gerais, compared to IN 76, did not fully met the legislation in all evaluated parameters.